Navigating Sense of Place through lived spaces and the memory of place in historic Anarkali Bazaar, Lahore - Zunaira Batool; Azizi Bahauddin (Built Heritage)
Abstract Historic fabric are increasingly at risk because they disregard the sense of place in urban regeneration projects, which jeopardises regional identities and customs. This study explores the processes underlying the creation of place meanings among users in historic urban bazaars, examining the attributes of lived space that contribute to the development of a sense of place and generate meaning through behavioural practices. Using the lived space of spatial triad theory as a theoretical framework, this research employs a hybrid methodological approach that combines phenomenological and grounded theory methods. Data are collected through semistructured interviews, onsite observations, and questionnaires, with analysis conducted via N-Vivo. By employing the lived space of spatial triad theory, this research offers a nuanced perspective on how historic urban bazaars function as living museums that foster pluralistic societies, cultural innovation, and economic fluidity within a contemplative environment. These insights underscore the importance of incorporating local memories and feelings into heritage conservation and urban regeneration projects, as these elements are crucial for maintaining the unique identity and vibrancy of historic sites. This study contributes to international scholarship on the lived space of historical sites by providing a focused examination of the dynamic forces shaping sense of place identity over time in historic bazaars.